The legal context and status of health foods - Coutrelis, N; Juchet, P (Oléagineux corps gras lipides, 2001)
One of the problems encountered when talking about health foods is the lack of common definition. We can consider that they include traditional foods with health claims, functional foods, fortified traditional foods, food intended for a particular nutritional use (PARNUT) and foods supplements. In European law, all products necessarily need to be defined either as foodstuff or as medicine. Consequently, practical questions must be borne in mind when marketing foodstuffs in the EU: is it a food, to which category of food does it belong, and are there any particular regulations applying to this product? According to the legal nature of the product, one should examine under which system and, if needed, under which procedure it can be marketed. The principle is that for foodstuffs in general, marketing is free, without pre-market approval or prior declaration and under the sole responsibility of the person responsible for the first marketing of the product (manufacturer or importer), only subject to a posteriori controls. However, new substances are subject to pre-market approval, according to various procedures depending on the case (EU procedure for novel foods, French procedure under the Decret of 1912). Concerning the presentation of the product, it is also necessary to determine to which category the product belongs, because some particular labelling rules may apply. In any case, claims should not be misleading. It is also prohibited to attribute to any foodstuff the property of preventing, treating or curing a human disease, or refer to such properties. Nutrition facts are not mandatory in general, but they are (and in that case they are strictly regulated) when a nutrition claim is made. Health claims in general are presently a highly debated topic